Productos financieros y su impacto al cliente objetivo de la Cooperativa de Ahorro y Crédito Kisapincha Ltda. de la ciudad de Ambato en el año 2023-2024. - Nauque Hernandez, Kevin Joel (2026)
The present Research analyzed the impact of financial services offered by the “Cooperative of Ahorro and credit Kisapincha Ltda”, in the city of Ambato during the period 2023-2024. Based on surveys applied to 234 members, strengths and weaknesses in the service offering were identified, which made it possible to propose strategies to improve service quality, foster financial education, and promote economic inclusion. Chapter I, it was identified that the financial products did not fully meet the clients’ real needs, therefore assessing their impact was proposed. Chapter II compiled theoretical foundations on loans, microloans, and savings, along with the analysis of the client profile. Chapter III described the mixed-method methodology based mainly on surveys. Chapter IV presented results showing frequent use of loans but also limitations in accessibility, clarity of information, and personalization. Chapter V, it was concluded that it was necessary to redesign the products and integrate digital tools and financial education. Chapter Chapter VI, proposed a strategic plan with actions to improve services, communication, and partnerships, strengthening the member experience and social impact.